Elleanthus ligularis, a name for a relatively common "new" sepecies of Elleantus sect. chloidelyna - L. Dressler, Robert (2007)
Elleanthus ligularis is described and illustrated. The flowers of this species are apparently selfpollinating. Fruiting material has been collected in Colombia, Costa Rica, Cuba and Panamá, but the species remained nameless in the absence of flowers, and is here described as Elleanthus ligularis. Costa Rican plants in cultivation have flowered in late December, January, February and April. The species is similar to E. graminifolius, but the plants are more robust, with wider leaves and the blade of the lip is subquadrate, rather than obtriangular, with a very short base.